2007
DOI: 10.1080/08039480701352546
|View full text |Cite
|
Sign up to set email alerts
|

The role of life events in social phobia

Abstract: The aim was to investigate the relationship between life events and social phobia. An inventory assessing life events during childhood, adulthood as well as life events experienced in relation to the onset of the disorder was administrated to 30 subjects with a DSM-IV diagnosis of social phobia. They were recruited by announcement and diagnosed by the Structured Clinical Interview for DSM-IV for axes I and II disorders. Seventy-five controls were selected by matching age and gender from the local population re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
21
2
Order By: Relevance
“…Congruent to earlier findings [1,19] the results of the present study showed that anxiety-disordered children experience significantly more negative life events compared to their non-anxious counterparts. Adjusted for the 'lifetime' experience of negative life events, anxiety-disordered, and non-anxious children differed in their use of cognitive coping strategies.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Congruent to earlier findings [1,19] the results of the present study showed that anxiety-disordered children experience significantly more negative life events compared to their non-anxious counterparts. Adjusted for the 'lifetime' experience of negative life events, anxiety-disordered, and non-anxious children differed in their use of cognitive coping strategies.…”
Section: Discussioncontrasting
confidence: 93%
“…Cognitive coping is considered to act as a mediator and moderator of the association between stress and psychological well being [6,7]. Cognitive coping might be particularly important to examine in relation to childhood anxiety disorders, as anxiety-disordered children experience significantly more stressful situations (i.e., negative life events) than their non-anxious counterparts and perceive these situations as more threatening [1,13,19]. Maladaptive or excessive use of cognitive coping strategies might contribute to the development and persistence of anxiety disorders in children.…”
Section: Introductionmentioning
confidence: 99%
“…Our result of enhanced responding to both CS-types in an anxious mood indicates that an individual in an anxious state would need more extinction trials (or exposure sessions) to reach the same effect as individuals in a neutral or happy emotional state. This interpretation is plausible given several studies revealing an association between the onset of anxiety disorders and a stressful period in the individual's life (Last, Barlow, & Obrien, 1984;Magee, 1999;Marks, 1987;Marteinsdottir, Svensson, Svedberg, Anderberg, & Von Knorring, 2007;Munjack, 1984). Individuals who experience stressful life events at the time of the aversive experience will have relatively enduring elevated background anxiety levels that may attenuate the normal recovery process through higher responsivity to cues associated with aversive contexts, which might increase the period of recovery compared to individuals without stressful life events, resulting in the worst case in a full-blown Anxiety Disorder.…”
Section: Discussionmentioning
confidence: 88%
“…In Sweden, a recent study comparing SAD patients and controls in terms of the frequency and impact of life events across different periods of life, also suggested a possible role for negative interpersonal events in the development of SAD. 27 Analyses of the combined sample as well as data from South Africa and Sweden separately, suggest that emotional abuse might be predictive of SAD vs. PD in later life. Some other studies have suggested a relation between childhood emotional abuse history and the presence of anxiety disorders, particularly SAD, in adulthood.…”
Section: Discussionmentioning
confidence: 99%